The interdependence of nuclear structure and function. - Iborra, F; Cook, P (2002)
2001 was the year of the human genome, but the new information has had little immediate impact on the field of nuclear structure. Rather, functional studies - especially on transcription - are leading us to a better understanding of how genomes might organise themselves into structures we call nuclei.